GENDER DALAM PERSPEKTIF ISLAM - Rusdi Zubeir (An Nisa'a, 2012)
Historically and factually, the status of women always goes through changes. In a society following a patriarchal paradigm, the position of women is less beneficial because they are in a suborniate position below men. Consequently, the position of women is always considered to be lower and they are subject to men. In addition, this assumption seems to get legitiation from theological doctrines, including al Qur'an and al Hadits which become the main sources of Islamic teachings. This article traces out the historical-theological root of gender inequality perspective of Moslem femeinist.